Fungitoxic effect of crude neem extract against Stemphylium vesicarium andits influence on seed yield and quality of onion - Niranjan Prasad, H P; Kumar, Atul; Akhtar, Jameel; Ranjan, Jeetendra Kumar; Dunna, Vijay; Mishra, Gyan Prakash; Rani, Shobha; Sushma, M K (Journal of Horticultural Sciences, 2025)
Stemphylium leaf blight, an emerging and economically devastating disease of onion crops, has prompted the search for eco-friendly alternatives due to stringent regulations with regard to synthetic fungicides. This study pioneers the comparative evaluation of Azadirachta indica crude extract against both six commercial fungicides (mancozeb, metiram + pyraclostrobin, difenoconazole, zineb, tebuconazole and kitazine) and two other botanicals (Lantana camara and Pongamia pinnata) under Indian field conditions. In vitro screening was conducted using the poisoned food technique at concentrations ranging from 100 to 2000 ppm, and field trials involved three foliar sprays at 10-day intervals on the onion var. Punjab Naroya. Under in vitro conditions, A. indica displayed >50% mycelial growth inhibition of Stemphylium vesicarium from concentrations as low as 250 ppm, outperforming all botanicals and most fungicides comparable only to triazole fungicides. Field trials demonstrated that A. indica (5%) reduced Stemphylium leaf blight disease severity by over 50%, with seed yield comparable to mancozeb and zineb. Notably, seeds treated with A. indica exhibited higher germination, improved vigour indices, and reduced electrical conductivity, indicating enhanced seed quality and membrane stability. By delivering disease control on par with leading synthetic fungicides without the associated environmental and resistance risks A. indica emerges as a potent, sustainable fungicidal alternative for onion seed production. The findings underscore its role in minimizing pesticide load while safeguarding both yield and seed quality, contributing to quality bulb and seed production.
Keywords: Allium cepa; fungicides; neem extract; seed quality; Stemphylium vesicarium